Association of Body Mass Index and Renal Size among Nepalese Healthy Adults in Terai Region - Sah, Nilam; Shrestha, Shamsher; Singh, Nutan Bala; Yadav, Sudeep Kumar; Pandit, Rakesh Kumar (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: The prognosis and diagnosis of renal disorders and diseases, as well as the assessment of kidney donors, both utilize ultrasound as a crucial imaging modality. Also, higher BMI is associated with the presence and development of proteinuria in individuals without kidney disease. Therefore, the purpose of this study was to determine the relationship between BMI and renal size by ultrasound imaging in healthy individuals at Janaki Medical College Teaching Hospital, Janakpurdham, Nepal. Material and Methods: This descriptive-analytical and cross-sectional study was carried out at Janaki Medical College Teaching Hospital, Nepal. All cases that referred for ultrasound were first measured by height and weight and their BMI was calculated. The size of the kidney length and the thickness of the kidney cortex were measured in millimeters. P-value less than 0.05 were considered statistically significant. Results: There were 110 females and 98 (47.1%) males. The range of ages was 18 to 70, with a mean age of 34.14 (SD 12.6). Both sexes have average BMIs of 23.39 (SD 4.06, range 15.5-36.1). Male subjects mean BMI is 23.705 (SD 3.5907, range 18.1-32.6), while female subjects' mean BMI is 23.108 (SD 4.44, range 15.5-36.1). The difference in BMI was not statistically significant (p = 0.291).Right kidney thickness and right and left cortical thickness were statistically significant (P <0.005). Age and renal length and renal cortex thickness were inversely correlated, although height and weight and renal length and renal cortex thickness were positively associated (p = 0.005). The length of the kidney and the thickness of the renal cortex, however, did not significantly correlate with BMI (P <0.05). Renal length and renal cortex thickness were negatively correlated with age, while there was a positive correlation between renal length and renal cortex thickness with positive correlation height and weight (p = 0.005). However, no significant correlation was found between the length of the kidney and the thickness of the kidney cortex with the BMI (P <0.05). Conclusion: A relationship between the increase in kidney length and kidney cortex with the weight and height of individuals, while this relationship was not observed in body mass index. Mean renal size is related to the side, age, gender, height and weight as well.